Produtividade do trabalho nos setores formal e informal no Brasil: Uma avaliaç\~ao do período recente - Gabriel Coelho Squeff (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– In this paper we discuss the evolution of labor productivity in the formal, informal and other households units sectors disaggregated by economic activity. Based on a modified shift-share that deals with the loss of additivity problem, we found that aggregate productivity grew 7% between 2001 and 2009 due to the formal sector - once informal activities contributed negatively - and positive contributions of productivity within activities (direct effect) and from occupation's composition (occupation effect). By excluding activities with high share of non-mercantile and imputed in total production, we found different results: aggregate productivity growth was only 2.2%, lower positive contribution from the formal sector, negative direct effect and positive occupation effect. Thus, it is urgent to adopt public policies in order to reduce informality and to promote a structural change in favor of higher added value activities.
Keywords: J24; O17; E01; 330; labor productivity; formal and informal sectors; national accounts